2021
DOI: 10.1007/s10549-021-06130-w
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated breast cancer: nationwide Dutch study confirms a discriminatory aggressive histopathologic profile

Abstract: Purpose Breast cancer is the most common type of malignancy in pregnant women, occurring approximately once in every 3000 pregnancies. Pregnancy-associated breast cancer (PABC) is commonly defined as breast cancer diagnosed during or within one year after pregnancy, and it accounts for up to 6.9% of all breast cancers in women younger than 45 years old. Whether these cancers arise before or during pregnancy, and whether they are stimulated by the high hormonal environment of pregnancy, is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
(33 reference statements)
3
19
0
4
Order By: Relevance
“…In our previous large population based study, triple negative breast cancer (TNBC: ER negative, PR negative, absence of HER-2 overexpression) was the most frequently observed subtype in PABC compared to age-matched non-PABC tumors [27], in line with other case control studies [14,18,28,29].…”
Section: Introductionsupporting
confidence: 84%
“…In our previous large population based study, triple negative breast cancer (TNBC: ER negative, PR negative, absence of HER-2 overexpression) was the most frequently observed subtype in PABC compared to age-matched non-PABC tumors [27], in line with other case control studies [14,18,28,29].…”
Section: Introductionsupporting
confidence: 84%
“…El cáncer de mama en el embarazo y lactancia es muy raro, ocurre con una frecuencia de 1 cada 3 000 a 10 000 embarazos, siendo el 1 % a 3 % de todos los cánceres de mama. Se define como carcinoma de mama asociado al embarazo o cáncer gestacional (CG) (23,24). Epidemiología: El CG se define como el cáncer de mama que ocurre durante el embarazo o un año después de este, representa el 6,9 % de todos los tumores en menores de 45 años y 15,6 % en menores de 35 años.…”
Section: Tumores Malignosunclassified
“…For example, patients diagnosed with PABC are younger, suffer a more advanced stage, have larger tumour sizes and have more axillary lymph node metastasis than non-PABC patients [ 3 , 4 ]. The advanced TNM stage at diagnosis of PABC patients might be caused by high levels of oestrogen and progesterone during pregnancy and high levels of prolactin during lactation or delayed diagnosis that was due to physiological changes of the breast during pregnancy or lactation and pathological changes of breast cancer [ 10 , 11 ]. Studies about the most frequent molecular subtype in PABC did not reach a consistent conclusion, most studies about European and American PABC patients showed triple-negative breast cancer (TNBC) was the most frequent one, some studies about Asian PABC patients showed that Luminal B was the most frequent molecular subtype [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%